Study of Compatibility of the Ingredients at Pharmaceutical Development of Medicine Syrup - Voronkina, Alyona (Asian Journal of Pharmaceutics (AJP), 2018)
Context: In the process of pharmaceutical development of syrup based on glucosamine and levocarnitine, there was a need to check the compatibility of active pharmaceutical ingredients (APIs) with auxiliary substances, which are a part of the drug in the form of syrup. Aims: This study aims to study the compatibility of API among themselves and with commonly used excipients settings and design: Compatibility was tested with the accelerated method by creating a mixture of APIs and auxiliary substances. Materials and Methods: Substances of glucosamine hydrochloride, levocarnitine, and auxiliary substances (sorbitol, xylitol, fructose, citric acid, agar, glycerin, and sorbic acid) were used. Substances’ quality meets the requirements of the European Pharmacopoeia monographs and they have certificates of conformity of the European Pharmacopoeia. The quantitative determination of API in model mixtures was carried out with high-performance liquid chromatography method. Statistical analysis was used by the method of Microsoft Office Excel 2007. Results: Studies have shown the lack of physical-chemical interaction between API and excipients both immediately after mixing and after storage. Conclusions: The conducted studies did not reveal the interaction of API: Glucosamine hydrochloride and levocarnitine with each other and with selected adjuvants: Sorbitol, xylitol, fructose, citric acid, glycerol, agar, and sorbic acid, neither in dry form nor in aqueous solution. Determination of the compatibility of ingredients by the accelerated method in the created model blends is promising, convenient, and demonstrative in the development of a new medicinal product.